2020
DOI: 10.3390/plants9030293
|View full text |Cite
|
Sign up to set email alerts
|

Weed Seed Decay in No-Till Field and Planted Riparian Buffer Zone

Abstract: Field management practices can alter the physical and chemical properties of the soil, also causing changes to the seed bank. Alterations can also occur to the soil microbial community, which in turn can increase or diminish the process of weed seed decay. In this research, the issue of seed degradation was studied in an undisturbed and a no-till soil, trying not only to uncover where seeds are more degraded, but also to investigate the microbial activities that could be involved in this process. Six different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In the surface layer of a mature no-till soil, crop residues interact with the soil and affect physical, chemical, and biotic soil properties. Therefore, weed seeds could also be affected by this interaction [3,[49][50][51]. Given the complexity of the factors involved, more studies in no-till fields, with different weed species and different types and amounts of residues, are necessary to improve our knowledge of weed-residue cover interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In the surface layer of a mature no-till soil, crop residues interact with the soil and affect physical, chemical, and biotic soil properties. Therefore, weed seeds could also be affected by this interaction [3,[49][50][51]. Given the complexity of the factors involved, more studies in no-till fields, with different weed species and different types and amounts of residues, are necessary to improve our knowledge of weed-residue cover interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Chantre et al [59] demonstrated that seed decay increases as burial depth and period increase, and decay was further elevated by complementary water supply. Seed decay is highly affected by the activity of soil microorganisms influenced by the soil environment, including the soil temperature, moisture, and physicochemical properties [60,61]. Several studies have shown that the impact of fungicidal treatments on the survival of buried seeds is more pronounced in relatively wetter conditions [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there are both antagonistic and mutually beneficial interactions between different bacteria and fungi (Chee‐Sanford et al, 2006; Diakaki et al, 2022; Pollard, 2018; Truyens et al, 2015). Seed decay rate in soil can depend on the morphology and composition of the seeds as well as the cellulolytic microbial activity in the soil (Nikolić et al, 2018). Ullrich et al (2011) reported that in one of the experiments they performed, the half‐life of weed seeds was negatively correlated to microbial biomass (both bacteria and fungi).…”
Section: Introductionmentioning
confidence: 99%